A rational approach to improving titer in Escherichia coli‐based cell‐free protein synthesis reactions. (19th August 2020) - Colant, Noelle; Melinek, Beatrice; Teneb, Jaime; Goldrick, Stephen; Rosenberg, William; Frank, Stefanie; Bracewell, Daniel G.
Abstract: Cell‐free protein synthesis (CFPS) is an established method for rapid recombinant protein production. Advantages like short synthesis times and an open reaction environment make CFPS a desirable platform for new and difficult‐to‐express products. Most recently, interest has grown in using the technology to make larger amounts of material. This has been driven through a variety of reasons from making site specific antibody drug conjugates, to emergency response, to the safe manufacture of toxic biological products. We therefore need robust methods to determine the appropriate reaction conditions for product expression in CFPS. Here we propose a process development strategy for Escherichia coli lysate‐based CFPS reactions that can be completed in as little as 48 hr. We observed the most dramatic increases in titer were due to the E. coli strain for the cell extract. Therefore, we recommend identifying a high‐producing cell extract for the product of interest as a first step. Next, we manipulated the plasmid concentration, amount of extract, temperature, concentrated reaction mix pH levels, and length of reaction. The influence of these process parameters on titer was evaluated through multivariate data analysis. The process parameters with the highest impact on titer were subsequently included in a design of experiments to determine the conditions that increased titer the most in the design space. This proposed process development strategy resulted in superfolder green fluorescent protein titers of 0.686 g/L, a 38% improvement on the standard operating conditions, and hepatitis B core antigen titers of 0.386 g/L, a 190% improvement.